Suunnitteluprojekti osana onnistunutta sosiaali- ja terveydenhuollon tietojärjestelmän käyttöönottoa. Case: Aster-projekti - Hilama, Pirjo; Mäkelä, Antti; Syväoja, Pirjo (Finnish Journal of eHealth and eWelfare, 2021)
During 2020–2026, the Aster project will implement the planning and actual implementation of the new customer and patient information system (CPIS) in cooperation between two hospital districts and two joint municipal authorities for health and social services. The benefit of joint procurement is the opportunity to use the diverse expertise of professionals working in the participating organizations and the extensive use of common resources. The new system is intended to seamlessly serve professionals working in social and health care, citizens who use the services and organizations that provide services. The planning phase, which will continue until September 2021, is important for the capability of the new system, as it will be used to refine and review in more detail the system requirements defined during the tendering phase. The requirements have been assessed in the national, regional and on a local context. According to the plans, the Aster project will enter the delivery phase from the beginning of 2022 and the first implementation of the new customer and patient system will take place in 2024.